2021
DOI: 10.3390/molecules26092417
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antidiabetic Activity of Proanthocyanidins from Fagopyrum dibotrys

Abstract: Proanthocyanidins are natural glycosidase inhibitors with excellent antioxidant activity. This study aims to search for a new source of proanthocyanidins for the prevention and treatment of type 2 diabetes with higher content and better activity and get their structure elucidated. First, the total proanthocyanidins contents (TOPCs), antioxidant activity, antidiabetic activity of seven common Polygonaceae plants were analyzed and compared. Then proanthocyanidins from the rhizome of Fagopyrum dibotrys were purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 55 publications
3
25
1
Order By: Relevance
“…The previous studies reported that H. fomes contains procyanidins and proanthocyanidins, [7] which facilitate insulin secretion from pancreatic β-cells. [50][51][52][53][54][55][56] Procyanidins also promote GLUT4 translocation in the muscle tissue via phosphorylation of AMPK and downstream signalling in ICR mice. [53] Additionally, epicatechin has antioxidant and insulinogenic activity, and it also has insulin-like properties.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies reported that H. fomes contains procyanidins and proanthocyanidins, [7] which facilitate insulin secretion from pancreatic β-cells. [50][51][52][53][54][55][56] Procyanidins also promote GLUT4 translocation in the muscle tissue via phosphorylation of AMPK and downstream signalling in ICR mice. [53] Additionally, epicatechin has antioxidant and insulinogenic activity, and it also has insulin-like properties.…”
Section: Discussionmentioning
confidence: 99%
“…Procyanidins are major found in dark-colored fruits including cherry, grape, pomegranate, and blueberry (Ho et al, 2020). As antioxidant, anticancer, antibacterial, and anti-diabetic, procyanidins attract attention in the field of food and pharmacology (Li et al, 2021;Nawrot-Hadzik et al, 2021) Studies showed that the consumption of procyanidin-rich foods can lower the incidence of inflammatory diseases (Williams et al, 2004). Procyanidins (200-400 mg/kg) can inhibit XO activity and reduce serum uric acid levels in hyperuricemia mice in a dose-dependent manner (Wang et al, 2004).…”
Section: Procyanidinsmentioning
confidence: 99%
“…The rhizome, as the medicinal tissue of golden buckwheat, is rich in various medicinal and hygienical components such as flavonoids (catechin and epicatechin), antioxidant phenolic compounds, γaminobutyric acid, and terpenoids (Shao et al, 2005;Wang et al, 2005;Zhang et al, 2016). Among these, flavonoids are some of the most functionally valuable components beneficial to health that are good for gastrointestinal dysfunction; enhance vascular toughness; reduce blood sugar, blood fat, and inflammation; promote tumor inhibition; and improve immunity (Chan, 2003;Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Proanthocyanidins are plant polyphenols formed by the condensation of flavane-3-ol monomers such as catechin and epicatechin (Li et al, 2021). They are the last components in flavonoid biosynthesis and essential bioactive components in golden buckwheat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation